Post mortem semen collection for human assisted reproduction and children’s rights - Cunha, Marcia Raquel Panunto Dias; Dantas Filho, Venâncio Pereira; Sardinha, Luiz Antonio da Costa; Zambelli, Helder José Lessa; Athayde, Maria Valéria de Omena; Sardinha, Yliah Cavalcanti; Rodrigues, Simey de Lima Lopes; Munhoz, Derli Conceição; Boin, Ilka de Fátima Ferreira (Brazilian Journal of Transplantation, 2021)
The authors describe two cases of requests, by wives, for post-mortem semen collection, in patients diagnosed with brain death, for later use in assisted human reproduction. In view of the unusual situation, an ethical and legal assessment of the characters involved in the process was carried out, with special attention to the child to be generated, their legal status and line of succession, and the best ethical posture to be taken by the medical professional involved in the process.